(untitled) (Bangladesh Journal of Medical Microbiology, 2016)
In this prospective study, among 47 clinically suspected cases of Liver abscess, 46 were diagnosed as of Amoebic origin. Confirmation of Amoebic Liver abscess (ALA) was done by ribosomal RNA (rRNA) gene detection from Liver abscess pus using real-time Polymerase Chain Reaction (PCR). In addition, microscopy for detection of the parasite in Liver abscess pus, and Lectin antigen as well as anti-Lectin antibody were detected by Enzyme Linked Immunosorbent Assay (ELISA) from both abscess pus and sera samples. Microscopically, 05 (10.89%) samples were found positive for motile Entamoeba histolytica and E. histolytica rRNA gene were detected in 46 (97.8%) cases by real-time PCR. Among the 47 Liver abscess pus, 12 (25.54%) were E. histolytica Lectin antigen positive and 4/47 (8.51%) of the sera samples were positive for E. histolytica Lectin antigen by ELISA. AntiLectin IgG was found positive in 91% (43/47) of the sera investigated. Reviewing the test results, it appears that detection of anti-Lectin IgG by ELISA may be considered as a useful, rapid and convenient immunological tool for the diagnosis ofALA cases. Bangladesh J Med Microbiol 2008; 02 (02): 27-30